2013
DOI: 10.1007/s00192-013-2286-5
|View full text |Cite|
|
Sign up to set email alerts
|

Interrater reliability of assessing levator ani deficiency with 360° 3D endovaginal ultrasound

Abstract: Our study demonstrates excellent agreement between raters assessing levator ani muscle deficiency using 3D endovaginal ultrasound. This level of concordance supports the reliability of the 3D endovaginal ultrasound technique and scoring method among raters [corrected].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…The results showed that the rhabdomyosphincter contracted synergistically with the levator ani muscle during all maneuvers except abdominal contraction [25]. Several studies have established the reliability of ultrasonography in the evaluation of both the levator ani muscles [11,12] and urethral sphincter complex [16,15,29] as independent structures. However, the morphologic relationship between the two has not been investigated using ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results showed that the rhabdomyosphincter contracted synergistically with the levator ani muscle during all maneuvers except abdominal contraction [25]. Several studies have established the reliability of ultrasonography in the evaluation of both the levator ani muscles [11,12] and urethral sphincter complex [16,15,29] as independent structures. However, the morphologic relationship between the two has not been investigated using ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…Based on published studies [3,11,12], the levator ani muscle was divided into three subgroups: the puboperinealis/puboanalis (PA), the puborectalis (PR), and the iliococcygeus/pubococcygeus (PV). The PA subgroup, which is poorly studied, is the perineal stabilizer, while the PR is the squeezer, and the PV is the elevator.…”
Section: Levator Ani Muscle Scoring Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…By using the same 360°rotational mechanical probe as used for EAUS, this procedure provides 3D high-resolution images of the anatomical structures of the pelvic floor [13]. It allows assessment of female urethral complex [14], biometric indices of the levator hiatus [15], damage of the levator ani [16], endopelvic fascia and/or the perineal body [17].…”
mentioning
confidence: 99%